They're real and they're here: the new federally regulated privacy rules under HIPAA...this article originally appeared in MEDSURG Nursing, 12(6), 380-385, 414 and is reprinted here with permission of the publisher - Frank-Stromborg M (Urologic Nursing, 2004)
The purpose of the HIPAA Privacy Rules was to create national standards to protect the privacy of personal health information. As of April 14, 2003, all covered health care entities must comply with the newly implemented national standards. The importance of staying updated with the law, while particularly important for the patient's privacy, is just as important for the nurse to avoid civil punitive damages and possible criminal charges.